2004
DOI: 10.1128/jvi.78.10.5045-5055.2004
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Integrase during Reverse Transcription of Human Immunodeficiency Virus Type 1 and the Effect of Cysteine Mutations of Integrase on Its Interactions with Reverse Transcriptase

Abstract: Retroviral integrase catalyzes the essential step of integrating a double-stranded DNA copy of the viral genome into a host cell chromosome. Mutational studies have revealed that integrase is involved in additional steps of viral replication, but the mechanism for the pleiotropic effect is not well characterized. Since Cys residues generally play crucial roles in protein structure and function, we introduced Cys-to-Ser substitutions at positions 56, 65, and 130 of human immunodeficiency virus type 1 (HIV-1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
161
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(176 citation statements)
references
References 61 publications
12
161
1
2
Order By: Relevance
“…The non-infectivity of viruses harboring the C130S IN protein was attributed to a viral failure to initiate the reverse transcription process [7]. This provided evidence that the IN-RT interaction is functionally critical for viral replication, and the C130S substitution indirectly abolished the contacts between the IN C-terminal domain and RT [7]. Another substitution at this position, C130A, exhibited wild-type replication kinetics [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-infectivity of viruses harboring the C130S IN protein was attributed to a viral failure to initiate the reverse transcription process [7]. This provided evidence that the IN-RT interaction is functionally critical for viral replication, and the C130S substitution indirectly abolished the contacts between the IN C-terminal domain and RT [7]. Another substitution at this position, C130A, exhibited wild-type replication kinetics [19].…”
Section: Discussionmentioning
confidence: 99%
“…Coimmunoprecipitation studies revealed that WT IN interacted with reverse transcriptase (RT) via its C-terminal domain, but the interaction was abolished in C130S mutant IN proteins. The non-infectivity of viruses harboring the C130S IN protein was attributed to a viral failure to initiate the reverse transcription process [7]. This provided evidence that the IN-RT interaction is functionally critical for viral replication, and the C130S substitution indirectly abolished the contacts between the IN C-terminal domain and RT [7].…”
Section: Discussionmentioning
confidence: 99%
“…The C130S and nonconservative W132 substitutions create structural perturbations that disrupt multimer formation and therefore the binding interactions between these inhibitors and the peptide region 128 AAC-WWAGIK 136 in the context of a multimeric IN structure. Structural perturbations caused by C130S have been documented and proposed to disrupt other processes, but not inhibitor binding (22)(23)(24). Substitutions made at amino acid residue W131 (W131D and W131E) have been shown to increase the solubility of IN fragments, enhancing their ability to crystallize, without effecting protein structure (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…After entry into the host cell cytoplasm, the HIV-1 core, containing the viral genomic RNA, RT, and integrase (IN), reorganizes to form the reverse transcription complex (RTC). The RTC requires both IN and RT to be active (5), and they are believed to recruit cellular factors to facilitate DNA synthesis (6). Although two-hybrid library and genomewide RNAi screening methods have implicated more than 50 cellular proteins as important for reverse transcription (6,7), whether any of these cellular proteins are RTC components, or whether they direct the RTC in other ways, is unclear.…”
mentioning
confidence: 99%